2017
DOI: 10.1111/sji.12621
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Prenatal Diagnosis of Chronic Granulomatous Disease: A Useful Tool in The Absence Of Molecular Diagnosis

Abstract: Chronic granulomatous disease (CGD) is an inherited immunodeficiency disorder affecting the microbicidal function of the phagocytes. It is characterized by susceptibility to recurrent infections leading to significant morbidity and mortality. Antibacterial and antifungal prophylaxis, though, has significantly reduced the rate and severity of the infections; the breakthrough infections still remain a challenge. Currently, allogenic haematopoietic stem cell transplantation is the only curative option which is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…To date, we detected CYBB variants in CGD patients, mostly involving exons 7 and 9, similar to that of previous studies . Mutation analysis remains an important tool for genetic counseling and prenatal diagnosis . Except for the CYBB variant, a previous study has shown that there are at least three types of AR‐CGD, which include NCF1 (20%), NCF2 (5%), and CYBA (5%) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To date, we detected CYBB variants in CGD patients, mostly involving exons 7 and 9, similar to that of previous studies . Mutation analysis remains an important tool for genetic counseling and prenatal diagnosis . Except for the CYBB variant, a previous study has shown that there are at least three types of AR‐CGD, which include NCF1 (20%), NCF2 (5%), and CYBA (5%) .…”
Section: Discussionsupporting
confidence: 84%
“…8,23 Mutation analysis remains an important tool for genetic counseling and prenatal diagnosis. 24 Except for the CYBB variant, a previous study has shown that there are at least three types of AR-CGD, which include NCF1 (20%), NCF2 (5%), and CYBA (5%). 8 However, in our study, we found AR-CGD is rare in Chinese pediatric patients, and CYBA is more common than the other two types.…”
Section: Discussionmentioning
confidence: 99%
“…This variant was identified as the molecular cause of the disease and abnormal neutrophil respiratory burst function was also observed. In recent years, flow cytometry has been used for the pre-natal diagnosis of CGD (23). Flow cytometry is a fast and sensitive method for detecting CGD; however, the accuracy of this method requires further evaluation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a genotype could not be identified using flow cytometric evaluation in two patients. In a country like India with limited resources, the predominance of AR-CGD type, and a high frequency of consanguineous marriages, the flow cytometric classification of CGD patients remains a vital tool in the early diagnosis and guide for molecular characterization (by suggesting appropriate method) (44, 68) (Figure 9).…”
Section: Chronic Granulomatous Diseases (Cgd)mentioning
confidence: 99%
“…Molecular diagnosis may not be possible or available in all affected cases; thus, phenotypic prenatal diagnosis by cordocentesis for families with an index case having an immunophenotypically well-characterized PID is an apt alternative. Thus, phenotypic prenatal diagnosis by flow cytometry offers a simple and rapid tool compared to molecular characterization (68, 69).…”
Section: Prenatal Diagnosis Using Flow Cytometrymentioning
confidence: 99%